Nexus tablets for dummies - Gookin, Dan (John Wiley & Sons, Inc, 2014)
Leverage the power of Google's revolutionary Nexus tablet with help from Dan Gookin and For Dummies Google's Nexus tablet is gaining market share at a rapid rate and offers a fantastic feature set at a price that is sure to please gamers, movie-watchers, e-book fans, and casual tablet users alike. Legendary For Dummies author Dan Gookin reviews all your tablet's features in this friendly guide, showing you just how to take advantage of the Nexus tablet you know and love. From using the built-in web browser to buying and downloading e-books, watching streaming video, taking and sharing photos and more.